Pupils’ Bullying at School is Not Related to Child-Parent Relationship: Empirical Evidence from the Philippines - Babor, Jezel; Albina, Albert; Luyas, Uniza; Azuelo, John Moses; Dagle, Carmela; Trinidad, Jessa Mae (Scholar: Human Sciences, 2025)
Purpose: This study investigates the extent of bullying among sixth grade pupils at a public school in Negros Oriental, Philippines, and analyze whether or not bullying at school among pupils is related to child-parent relationship. Research design, data, and methodology: The sample participants of this study consisted of 85 pupils who came from three sections of grade six and 85 parents of these pupils. This study employed a quantitative-descriptive design using self-administered questionnaires to obtain robust data to address the research questions. The questionnaires used were the Olweus Bully/Victim Questionnaire (OBVQ) and Child-Parent Relationship Scale (CPRS). Results: The results reveal that bullying only happened once or twice a month. Further, the extent when pupils were bullied, and the extent when they were bullies were found to be positively correlated, r (83) = .548, p < .001. There is also no relationship between the extent of bullying and child-parent relationship. Conclusion: Parents positive interaction with their children does not guarantee that their child will not commit bullying and also to the parents that have negative interaction with their children does not mean that their child will be bullies. Thus, child-parent relationship has nothing to do with the bullying that occurs in school.